Usage of the online platform teams for organizing independent work during practical classes of medical faculty students - Ivanchenko, O. Z.; Melnikova, O. Z.; Lurie, K. I.; Іванченко, Олена Зенонівна; Мельнікова, Оксана Зенонівна; Лур'є, Костянтин Ігорович (My University, 2023)
The article analyzes the advantages and disadvantages of distance learning in the modern educational process, as well as the conditions for optimal quality organization of independent work of medical faculty students in practical classes. The article formulates the main requirements for creating tasks for the Forms application of the Microsoft Teams online platform, the implementation of which contributes not only to the reproductive recreation of knowledge but also to the development of the ability to analyze, think, draw conclusions and use one's knowledge in practice.
Keywords: independent work; online training; Forms application